Role of Ten eleven translocation‐2 (Tet2) in modulating neuronal morphology and cognition in a mouse model of Alzheimer's disease. Issue 4 (30th November 2020) - Li, Liping; Miao, Miao; Chen, Jiarui; Liu, Zhitao; Li, Wanyi; Qiu, Yisha; Xu, Shujun; Wang, Qinwen
Abstract: Abnormal expression of Ten eleven translocation‐2 (Tet2) contributes to the pathogenesis of Alzheimer's disease (AD). However, to date, the role of Tet2 in modulating neuronal morphology upon amyloid‐β (Aβ)‐induced neurotoxicity has not been shown in a mouse model of AD. Here, we have developed a model of injured mouse hippocampal neurons induced by Aβ42 oligomers in vitro. We also investigated the role of Tet2 in injured neurons using recombinant plasmids‐induced Tet2 inhibition or over‐expression. We found that the reduced expression of Tet2 exacerbated neuronal damage, whereas the increased expression of Tet2 was sufficient to protect neurons against Aβ42 toxicity. Our results indicate that the brains of aged APPswe/PSEN1 double‐transgenic (2 × Tg‐AD) mice exhibit an increase in Aβ plaque accumulation and a decrease in Tet2 expression. As a result, we have also explored the underlying mechanisms of Tet2 in cognition and amyloid load in 2 × Tg‐AD mice via adeno‐associated virus‐mediated Tet2 knockdown or over‐expression. Recombinant adeno‐associated virus was microinjected into bilateral dentate gyrus regions of the hippocampus of the mice. Knocking down Tet2 in young 2 × Tg‐AD mice resulted in the same extent of cognitive dysfunction as aged 2 × Tg‐AD mice. Importantly, in middle‐aged 2 × Tg‐AD mice, knocking down Tet2 accelerated the accumulation of Aβ plaques, whereas over‐expressing Tet2 alleviated amyloid burden and memory loss. Furthermore, our hippocampal RNA‐seq data, from young 2 × Tg‐AD mice, were enriched with aberrantly expressed lncRNAs and miRNAs that are modulated by Tet2. Tet2‐modulated lncRNAs (Malat1, Meg3, Sox2ot, Gm15477, Snhg1) and miRNAs (miR‐764, miR‐211, and miR‐34a) may play a role in neuron formation. Overall, these results indicate that Tet2 may be a potential therapeutic target for repairing neuronal damage and cognitive impairment in AD. Abstract : We uncover an important role for Tet2 in the regulation of neuronal morphology and cognitive function in AD. Loss of Tet2 aggravates Aβ‐induced neuronal damage, whereas increasing Tet2 can rescue structural defects from Aβ toxicity in vitro. Decreasing Tet2 expression exacerbates cognitive dysfunction and Aβ plaque accumulation, whereas increasing Tet2 expression restores Aβ burden and memory loss in vivo. Tet2‐modulated lncRNAs (Malat1, Meg3, Sox2ot, Gm15477, Snhg1) and miRNAs (miR‐764, miR‐211, and miR‐34a) may be involved in AD related‐neuron deficits. Our data raise the exciting possibility that Tet2 and its downstream may serve as therapeutic targets for the treatment of AD.